2010
DOI: 10.1002/ange.201004318
|View full text |Cite
|
Sign up to set email alerts
|

Dichlorophenyl Derivatives of La@C3v(7)‐C82: Endohedral Metal Induced Localization of Pyramidalization and Spin on a Triple‐Hexagon Junction

Abstract: Einflussreicher Gast: Eine Röntgen‐Strukturanalyse belegt, dass der Dichlorphenylsubstituent der Titelverbindung über eine Einfachbindung mit einem Kohlenstoffatom am Schnittpunkt dreier Sechsecke verknüpft ist. Die Auftragung berechneter p‐Orbitalachsenvektor(POAV)‐Werte gegen die SOMO‐Spindichte weist für dieses C‐Atom einen ausgeprägt radikalischen Charakter infolge starker Metall‐Käfig‐Wechselwirkungen aus (siehe Graph).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…In the previous reports, 1,2,4-trichlorobenzene was used for extraction of La@C 2n (C 6 H 3 Cl 2 ) (n=36, 37, 40, 41) [6][7][8][9]. To reduce the number of possible isomers depending on the substituent, 1,2-dichlorobenzene, chlorobenzene, or iodobenzene was used as an alternative solvent for the extraction of fullerenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous reports, 1,2,4-trichlorobenzene was used for extraction of La@C 2n (C 6 H 3 Cl 2 ) (n=36, 37, 40, 41) [6][7][8][9]. To reduce the number of possible isomers depending on the substituent, 1,2-dichlorobenzene, chlorobenzene, or iodobenzene was used as an alternative solvent for the extraction of fullerenes.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, La@D 3h -C 74 (C 6 H 3 Cl 2 ), La@C 2v (3)-C 80 (C 6 H 3 Cl 2 ), and La@C 3v (7)-C 82 (C 6 H 3 Cl 2 ), were isolated and characterized by the single-crystal X-ray diffraction (XRD) crystallographic analyses [7][8][9]. Theoretical calculations showed that the carbon atoms at the sites of addition on these fullerenes always possess very high radical character.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several missing-cage species, namely, La@C 2n (2n = 72, 74, 80, 82), are solubilized and isolated as dichlorophenyl derivatives. [10][11][12][13] Herein we report our recent findings that addition of dichlorophenyl radical to La@C 74 actually generates two series of regioisomers of La@C 74 (C 6 H 3 Cl 2 ), each of which has been identified by X-ray crystallography. Our results show that two neighboring cage carbon atoms, both of which are very close to the internal metal atom, are highly reactive toward radicals as a result of strong metal-cage interactions.…”
mentioning
confidence: 88%
“…This is consistent with our previous conclusions that the substitution pattern of the dichlorophenyl group has a negligible effect on the electronic structures of the adducts. [13] In detail, the A, B, and C isomers of La@C 74 (C 6 H 3 Cl 2 )-I feature distinct absorption bands at 555, 740, and 1135 nm with an onset at 1350 nm, corresponding to a medium optical bandgap (0.92 eV). In contrast, the isomers with a substituent attached on Carbon II show absorption peaks at 630, 750, 960, and 1475 nm; the onset at 1690 nm indicates a relatively small bandgap (0.73 eV).…”
mentioning
confidence: 99%
See 1 more Smart Citation